Bruxism in children current landscape: literature review (Research, Society and Development, 2022)
In 2017, in an international consensus with experts in bruxism worldwide, bruxism was defined as a "repetitive activity of the jaw muscles characterized by clenching or grinding of the teeth and/or clenching or thrusting of the jaw". It was observed different characteristics while sleeping and vigil respectively. As different characteristics were observed during sleep and waking bruxism, sequentially, it is recommended to "withdraw" the single definition of bruxism in favor of two separate definitions. In this way, the objective of this article is to reflect the current view of bruxism to establish an adequate diagnostic as well as an optimal treatment based on the results obtained. This is descriptive research that includes a total of 25 articles. No significant differences have been found regarding gender, it is considered more a sign of a disease than a disorder and can present itself as a risk factor or as a protective factor; of multifactorial etiology. It is concluded that the treatment is focused depending on the etiological factor from a psychological approach to a surgical treatment, discarding preconceived ideas that may tend to overestimate the true scope of the particularities of bruxism.